The Penguin Roget's College Thesaurus in Dictionary Form - Morehead, Philip (New York Penguin Reference, 2001)
Since its first publication in 1958, The New American Roget's College Thesaurus has reached more than fifteen million copies in print. Now, as The Penguin Roget's College Thesaurus in Dictionary Form, it has been totally revised, reset, and modernized in both form and content -- for the first time ever. Its more than 1,500 new entries will keep users thoroughly up to date with today's expanding language, current colloquialisms, and slang expressions. It contains many more listings under a variety of entries, a listing of antonyms throughout, and the addition of categorized quotations. This larger format edition -- with an improved cross-referencing system and an increased quantity of double-column material -- is easier to use than ever before and remains the essential resource for students and writers of every stripe.
Keywords: English language -- Synonyms and antonyms -- Dictionaries -- English language -- Synonyms and antonyms -- Synonym